Testing the Monday Effect on IDX-30 Companies: Evidence from the Indonesia Stock Exchange : February 2018 - January 2023 - Laili Muslihah; Ernie Hendrawaty; Ahmad Faisol (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the presence of the Monday effect in companies listed in the IDX30 index on the Indonesia Stock Exchange (IDX) from February 2018 to January 2023. The Monday effect is a market anomaly where stock returns on Mondays tend to be systematically different from other trading days. This phenomenon, if proven, challenges the efficient market hypothesis. The main research problem is whether the Monday effect exists in IDX30 stocks during the specified period. The study aims to provide empirical evidence regarding this anomaly in the Indonesian stock market. The research employs a quantitative approach, utilizing secondary data in the form of daily stock closing prices. The sample consists of 15 companies that were consistently listed in the IDX30 index throughout the study period, selected through a purposive sampling method. The analysis is conducted using the One-Way ANOVA test with SPSS 27 statistical software to compare stock returns across different trading days. The findings confirm the presence of the Monday effect in IDX30-listed stocks, indicating that stock returns on Mondays exhibit statistically significant differences compared to other days. These results suggest that behavioral factors and market inefficiencies may influence stock price movements in the IDX30 index. This study contributes to the literature on stock market anomalies and provides insights for investors and policymakers regarding trading strategies and market efficiency in Indonesia.